1993
DOI: 10.1901/jeab.1993.59-61
|View full text |Cite
|
Sign up to set email alerts
|

A Transfer of Functions Through Derived Arbitrary and Nonarbitrary Stimulus Relations

Abstract: During Experiments 1 and 2, subjects were trained in a series of related conditional discriminations in a matching-to-sample format (A1-B1, A1-C1 and A2-B2, A2-C2). A low-rate performance was then explicitly trained in the presence of B1, and a high-rate performance was explicitly trained in the presence of B2. The two types of schedule performance transferred to the C stimuli for all subjects in both experiments, in the absence of explicit reinforcement through equivalence (i.e., C1 = low rate and C2 = high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
122
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 19 publications
9
122
0
4
Order By: Relevance
“…For example, when given all stimuli, a subject might first sort all class-1 stimuli in one group and then all class-2 stimuli in another group. It has been shown that stimulus equivalence is frequently, but not always, associated with functional equivalence, and vice versa (Barnes & Keenan, 1993;de Rose, Mcllvane, Dube, Galpin, & Stoddard, 1988;Dube, McDonald, & Mcllvane, 1990;Dymond & Barnes, 1994;Sidman, Wynne, Maguire, & Barnes, 1989;Smeets, Barnes, & Roche, 1997). How does sorting compare with functional equivalence?…”
Section: Discussionmentioning
confidence: 99%
“…For example, when given all stimuli, a subject might first sort all class-1 stimuli in one group and then all class-2 stimuli in another group. It has been shown that stimulus equivalence is frequently, but not always, associated with functional equivalence, and vice versa (Barnes & Keenan, 1993;de Rose, Mcllvane, Dube, Galpin, & Stoddard, 1988;Dube, McDonald, & Mcllvane, 1990;Dymond & Barnes, 1994;Sidman, Wynne, Maguire, & Barnes, 1989;Smeets, Barnes, & Roche, 1997). How does sorting compare with functional equivalence?…”
Section: Discussionmentioning
confidence: 99%
“…Research into function transfer in stimulus equivalence classes typically has involved training a relatively simple function to one member of a stimulus equivalence class (e.g., Barnes & Keenan, 1993). While there are good reasons for adopting this strategy, the findings reported here indicate that perhaps there have been hidden limitations to date in either the kinds of questions that can be asked or in the phenomena that can be uncovered.…”
Section: Discussionmentioning
confidence: 86%
“…Once a single operant function has been explicitly trained to a member of an equivalence class, subsequent tests usually demonstrate that this function is recorded in the presence of other members of that particular class (Barnes & Keenan, 1993;Lazar & Kotlarchyk, 1986;Wulfert & Hayes, 1988;Kohlenberg, Hayes & Hayes, 1991;Dougher, Auguston, Markham, Greenway & Wulfert, 1994). Because this finding has been so consistent it has not been necessary to inquire about the stability of trained functions.…”
Section: Stability Of Trained Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a wide variety of stimulus function transformations has been demonstrated in accordance with equivalence relations (e.g., Barnes & Keenan, 1993;Dougher, Augustson, Markham, Greenway, & Wulfert, 1994;Dougher, Perkins, Greenway, Koons, & Chiasson, 2002;Dymond & Barnes, 1995;Rehfeldt & Hayes, 1998;Smeets & Barnes-Holmes, 2003; see Dymond & Rehfeldt, 2000, for a review) and derived relations other than equivalence, such as Sameness, Opposition, and Difference (Dymond & Barnes, 1996;Steele & Hayes, 1991;Roche & Barnes, 1996Whelan & Barnes-Holmes, 2004), More than and Less than (Dymond & Barnes, 1995;O'Hora, Roche, Barnes-Holmes, & Smeets, 2002;Whelan, Barnes-Holmes, & Dymond, 2006), and Before and After (Barnes-Holmes, Hayes, Dymond, & O'Hora, 2001; O'Hora, Barnes-Holmes, Roche, & Smeets, 2004). For example, Roche and Barnes (1997) exposed participants to a relational pretraining procedure to establish contextual functions of Same and Opposite for two arbitrary stimuli.…”
mentioning
confidence: 99%